Difference between revisions of "008A Sample Final A, Question 11"

From Math Wiki
Jump to navigation Jump to search
Line 26: Line 26:
 
! Step 2:
 
! Step 2:
 
|-
 
|-
|Now we have the equality <math>\frac{3x^2 +6x + 7}{(x + 3)^2(x - 1)} = \frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>. Now clearing the denominators we end up with <math>A(x + 3)^2 + B(x - 1)(x + 3) + C(x - 1) = 3x^2 + 6x + 7</math>.
+
|Now we have the equality <math>\frac{3x^2 +6x + 7}{(x + 3)^2(x - 1)} = \frac{A}{x - 1} + \frac{B}{x + 3} + \frac{C}{(x + 3)^2}</math>. We clear the denominators and end up with <math>A(x + 3)^2 + B(x - 1)(x + 3) + C(x - 1) = 3x^2 + 6x + 7</math>.
 
|}
 
|}
  
Line 32: Line 32:
 
! Step 3:
 
! Step 3:
 
|-
 
|-
|To proceed we start by evaluating both sides at different x-values. We start with x = 1, since this will zero out the B and C. This leads to <math>A(1 + 3)^2 = 3(1)^2 + 6(1) + 7</math><math>16A = 3 + 6 + 7</math>, and finally A = 1.
+
|By evaluation both sides by using x = 1, we will zero out the B and C. This leads to <math>A(1 + 3)^2 = 3(1)^2 + 6(1) + 7,  16A = 3 + 6 + 7</math>&nbsp;, and finally <math>A = 1</math>.
 
|}
 
|}
  
Line 38: Line 38:
 
! Step 4:
 
! Step 4:
 
|-
 
|-
|Now evaluate at -3 to zero out both A and B. This yields the following equations <math>C((-3) - 1) = 3(-3)^2 + 6(-3) + 7</math>, <math>-4C = 3(9) - 18 + 7</math>, <math>-4C = 27 - 11</math>, and <math>C = -4</math>
+
|Now evaluating at x = -3 to zero out both A and B. This yields the following equations <math>C((-3) - 1) = 3(-3)^2 + 6(-3) + 7</math>, <math>-4C = 3(9) - 18 + 7</math>, <math>-4C = 27 - 11</math>, and <math>C = -4</math>
 
|}
 
|}
  
Line 44: Line 44:
 
! Step 5:
 
! Step 5:
 
|-
 
|-
|To obtain the value of B we  can evaluate x at any value except 1, and -3. We do not want to evaluate at 1 and -3 since both of these will zero out the B. Evaluating at x = 0 will make the arithmetic easier, and gives us <math>A(0 + 3)^2 + B(0 - 1)(0 + 3) + C(0 - 1) = 9A -3B -C = 7</math>. However, we know the values of both A and C, which are 1 and -4, respectively. So <math>9 -3B - (-4) = 7</math>, <math>-3B + 13 =  7</math>, <math>-3B = -6</math>, and finally <math>B = 2</math>. This means the final answer is <math>\frac{1}{x - 1} + \frac{2}{x + 3} - \frac{4}{(x + 3)^2}</math>
+
|To obtain the value of B we  can evaluate x at any value except 1, and -3. We do not want to evaluate at 1 and -3 since both of these will zero out the B. Evaluating at x = 0 will make the arithmetic easier, and gives us <math>A(0 + 3)^2 + B(0 - 1)(0 + 3) + C(0 - 1) = 9A -3B -C = 7</math>. However, we know the values of both A and C, which are 1 and -4, respectively. So <math>9 -3B - (-4) = 7</math>, <math>-3B + 13 =  7</math>, <math>-3B = -6</math>, and finally <math>B = 2</math>.
 
|}
 
|}
  

Revision as of 14:52, 23 May 2015

Question: Decompose into separate partial fractions

Foundations
1) How many fractions will this decompose into? What are the denominators?
2) How do you solve for the numerators?
Answer:
1) Since each of the factors are linear, and one has multipliclity 2, there will be three denominators. The linear term, , will appear once in the denominator of the decomposition. The other two denominators will be .
2) After writing the equality, , clear the denominators, and evaluate both sides at x = 1, -3, and any third value. Each evaluation will yield the value of one of the three unknowns.

Solution:

Step 1:
From the factored form of the denominator we can observe that there will be three denominators: , and . So the final answer with have the following form:
Step 2:
Now we have the equality . We clear the denominators and end up with .
Step 3:
By evaluation both sides by using x = 1, we will zero out the B and C. This leads to Failed to parse (MathML with SVG or PNG fallback (recommended for modern browsers and accessibility tools): Invalid response ("Math extension cannot connect to Restbase.") from server "https://wikimedia.org/api/rest_v1/":): {\displaystyle A(1 + 3)^2 = 3(1)^2 + 6(1) + 7, 16A = 3 + 6 + 7}  , and finally .
Step 4:
Now evaluating at x = -3 to zero out both A and B. This yields the following equations , , , and
Step 5:
To obtain the value of B we can evaluate x at any value except 1, and -3. We do not want to evaluate at 1 and -3 since both of these will zero out the B. Evaluating at x = 0 will make the arithmetic easier, and gives us . However, we know the values of both A and C, which are 1 and -4, respectively. So , , , and finally .
Final Answer:

Return to Sample Exam